Penyelesaian Kasus Kredit Macet Terhadap Perjanjian Pinjam Nama Atas Pelaksanaan Kredit Kepemilikan Rumah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The phenomenon of “name borrowing” in applying for a Home Ownership Loan (KPR) is often the root cause of problems in cases of bad credit. This study examines a case study at PT. BPR Paro Laba Tondano to analyze the legal implications of this practice and how it can be resolved. Using a normative approach and case study, it was found that legal responsibility remains with the party whose name is listed in the agreement, even if another party uses the facility. Resolution can be pursued through civil and criminal channels, and requires the bank to apply the principle of due diligence. This study highlights the need for legal education and stricter verification systems to prevent similar incidents.